Linguistic and Country Studies Learner’s Dictionary for Mongolian Citizens: Specifics of Presenting the Material - Alexander S. Mamontov; Enkhtuyaa Tsedendorzhiyn; Vera V. Boguslavskaya (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2019)
The article is devoted to the principles of nationally oriented lexicography - a new direction in Russian studies. Using the example of nationally oriented linguistic and country studies learner's dictionary project, the paper shows that it can be created on the basis of the Russian linguistic and country studies dictionary by adding Mongolian material to its content and by comparing lexical backgrounds of the same culture-specific concepts in two linguistic cultures. The purpose of the nationally oriented linguistic and country studies learner's dictionary – the explication of the cultural component of the language unit semantics, taking into account the specifics of the national culture and the language of the addressee at the same time and taking into account the stage of learning – is reflected in the content and structure of the dictionary in general and dictionary entries in particular. Selecting nominative units and providing vocabulary objectivity are determined by the addressee's communicative needs. The author uses the methods of semantization of lexical units adopted in educational lexicography and determined by the specifics of both the material and the addresse. The paper provides the characteristics of techniques that ensure compliance with the proportions in using target and native languages. The draft dictionary presented in the article is able to serve as a "starting point" in creating a new type of dictionaries and further developing fundamentals of the theory of nationally oriented educational linguistic and cultural lexicography in relation to the needs of teaching Russian as a foreign language in the absence of the language environment.